2003
DOI: 10.1128/mcb.23.10.3497-3505.2003
|View full text |Cite
|
Sign up to set email alerts
|

Two Ubiquitin-Conjugating Enzymes, UbcP1/Ubc4 and UbcP4/Ubc11, Have Distinct Functions for Ubiquitination of Mitotic Cyclin

Abstract: Cell cycle events are regulated by sequential activation and inactivation of Cdk kinases. Mitotic exit is accomplished by the inactivation of mitotic Cdk kinase, which is mainly achieved by degradation of cyclins. The ubiquitin-proteasome system is involved in this process, requiring APC/C (anaphase-promoting complex/ cyclosome) as a ubiquitin ligase. In Xenopus and clam oocytes, the ubiquitin-conjugating enzymes that function with APC/C have been identified as two proteins, UBC4 and UBCx/E2-C. Previously we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…The cold-sensitive nda3-KM311 mutation defective in the spindle formation 42 was introduced into each of the ubc11-P93L mutant, ubc4-P61S mutant 37 and ubc4-P61S ubc11-P93L double mutant, respectively. In the nda3-KM311 single mutant after incubation at its restrictive temperature (20°C), the three proteins accumulated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cold-sensitive nda3-KM311 mutation defective in the spindle formation 42 was introduced into each of the ubc11-P93L mutant, ubc4-P61S mutant 37 and ubc4-P61S ubc11-P93L double mutant, respectively. In the nda3-KM311 single mutant after incubation at its restrictive temperature (20°C), the three proteins accumulated.…”
Section: Resultsmentioning
confidence: 99%
“…The level of Cdc13, E2s, fission yeast Ubc11 and Ubc4, each of which has an essential and incompatible role in polyubiquitin-chain formation. 37 The B-type cyclin/Cdc13 and securin/Cut2 cause a mitotic arrest if not properly degraded in the APC/C-dependent manner. [38][39][40][41] We therefore attempted to examine how the ubc11-P93L mutation affects the stability of proteins normally degraded in the APC/C-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are forced to conclude that in mammalian cells UbcH10 is either not essential for the APC/C to ubiquitylate its substrates in mitosis -for example, the APC/C may be able to use UbcH5 and E2-25K, as it can in vitro (Rodrigo-Brenni and Morgan, 2007) -or UbcH10 is not rate limiting and the low levels remaining in the cells are sufficient for the normal kinetics of the APC/C. Completely eliminating UbcH10 might inactivate the APC/C because cells of vihar mutants in Drosophila arrest in mitosis with defective spindles (Mathe et al, 2004), and fission yeast cells lacking the UbcH10 orthologue UbcP4/Ubc11 are unable to degrade cyclin B (Cdc13) (Seino et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, an in vivo study showed that these two classes of E2 are not functionally equivalent but exhibit distinct functions in mitotic cyclin degradation, suggesting that different E2 family members probably execute distinct functions (Seino et al, 2003). The Drosophila ortholog of UBCx/E2-C, Vihar E2, has been reported to be involved in Cyclin B degradation during the metaphase-anaphase transition (Mathe et al, 2004).…”
Section: The Biochemical Role Of Eff In the Regulation Of Gscsmentioning
confidence: 99%